2017
DOI: 10.1007/s10096-017-3084-7
|View full text |Cite
|
Sign up to set email alerts
|

Methanobrevibacter smithii, a methanogen consistently colonising the newborn stomach

Abstract: Methanobrevibacter smithii is the main human methanogen almost always found in the digestive tract of adults. Yet, the age at which M. smithii establishes itself as part of the developing intestinal microflora remains unknown. In order to gain insight into this, we developed a polyphasic approach, including microscopic observation by fluorescence in situ hybridisation, polymerase chain reaction (PCR) sequencing detection, identification and culture, to isolate and genotype M. smithii in one-day-old newborns' g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 22 publications
4
67
0
2
Order By: Relevance
“…As for Methanobrevibacter, it is the main human methanogen that is almost always found in the digestive tract of adults, with colonization taking place just after birth. Methanobrevibacter is also the main CH 4 /H 2 O producer, which is carried out by transforming H 2 and CO 2 [41].…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 99%
“…As for Methanobrevibacter, it is the main human methanogen that is almost always found in the digestive tract of adults, with colonization taking place just after birth. Methanobrevibacter is also the main CH 4 /H 2 O producer, which is carried out by transforming H 2 and CO 2 [41].…”
Section: Changes Of Microbial Composition During Mango (Mangifera Indmentioning
confidence: 99%
“…Nevertheless, (methanogenic) archaea are part of the commensal microorganisms inhabiting the human body, being regularly detected in the oral cavity and the gastrointestinal tract (Chaudhary et al, 2015;Gaci et al, 2014;Horz and Conrads, 2011;Nkamga et al, 2017); in the latter they sometimes even outnumber the most abundant bacterial species (14%, (Tyakht et al, 2013);). Most human archaea studies use either cultivation or qPCR methods (Grine et al, 2017;Koskinen et al, 2017;van de Pol et al, 2017;Wampach et al, 2017) and only a few, 16S rRNA gene-based archaeacentric studies are available Moissl-Eichinger et al, 2017). These new studies have shown that archaea are also present in the human respiratory tract and on human skin in considerable amounts Probst et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the research on the commensal viral and fungal constituents of human microbiota gained momentum recently, most microbiota studies still fail to include the archaea. The studies on human archaeome usually employ either cultivation or qPCR methodology [118,119,148], while 16S rRNA gene-based research often uses bacterial-targeted protocols and universal primer pairs to cover the broadest prokaryotic diversity [119,149]. The low abundance of archaeal DNA in human samples, inefficient cell lysis and DNA extraction, failure of the universal primers to fully detect archaeal signatures, as well as incomplete 16S rRNA gene databases, all represent methodological pitfalls of human archaeome analysis [112,150,151].…”
Section: Human Archaeomementioning
confidence: 99%